Pengaruh Akuntabilitas, Transparansi Dan Pengawasan Terhadap Kinerja Pengelolaan Dana Bantuan Operasional Satuan Pendidikan (BOSP) Pada SDN Kecamatan Batukliang Kabupaten Lombok Tengah - Maolina Amelya Rosa; Martiningsih, Rr. Sri Pancawati (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to analyze the influence of accountability, transparency, and supervision on the performance of the management of the Operational Assistance Fund for Education Units (BOSP) at Public Elementary Schools (SDN) in Batukliang District, Central Lombok Regency. Problems in the management of BOSP funds that are often found include lack of information transparency, inaccurate reporting, and weak supervision in their use. This study uses a quantitative approach with data collection techniques through distributing questionnaires to respondents involved in the management of BOSP funds, such as principals, treasurers, and school committees. The data obtained were analyzed using multiple linear regression to test the effect of each independent variable on the dependent variable. The results of the study indicate that accountability and supervision have a positive and significant effect on the performance of BOSP fund management, while transparency has a negative and insignificant effect on the performance of BOSP fund management. This finding emphasizes the importance of implementing good governance principles in the management of education funds in order to increase the effectiveness and efficiency of the implementation of the BOSP program at the elementary education unit level.